Equilibrium short-rate models vs no-arbitrage models: Literature review and computational examples - Josheski, Dushko; Apostolov, Mico (Modele krótkoterminowe w równowadze a modele bez arbitrażu: przegląd literatury i przykłady obliczeniowe, 2021)
In this paper equilibrium short-rate models are compared against no-arbitrage short-rate models. This article is composed of the introduction to this literature and a review, followed by numerical examples of one-factor short-rate models; the Cox-Ingersoll-Ross (CIR) model and the Vasicek model. No-arbitrage models were presented through the Hull-White (HW) model, the Binomial lattice model for bond pricing and interest rate modelling, the Black-Karasinski (BK) model, and the Heath-Jarrow-Morton (HJM) model. The results prove that no single interest rate model exists that can be used for all purposes. These models were compared in terms of volatility, mean reversion process and convergence. The end results confirm the dependence of volatility on the level rate as a determinant of the predictive success of these models
Econometrics = Ekonometria, 2021, Vol. 25, No. 3, s. 42-71
Keywords: equilibrium models; one factor short-rate models; no-arbitrage models; Vasicek model; Hull-White model; Black-Karasinski model; Heath-Jarrow-Morton model; Cox-Ingersoll-Ross model; modele równowagi; jednoczynnikowe modele krótkoterminowe; modele bez-arbitrażowe; model Vasicka; model Hulla i White’a; model Blacka-Krasinskiego; model Heath-Jarrow-Morton; model Coxa-Ingersolla-Rossa